Molecular phylogeny of Asiatic Short-Tailed Shrews, genus Blarinella Thomas, 1911 (Mammalia: Soricomorpha: Soricidae) and its taxonomic implications - Chen, Shunde; Liu, Shaoying; Liu, Yang; He, Kai; Chen, Weicai; Zhang, Xiuyue; Fan, Zhenxin; Tu, Feiyun; Jia, Xiaodong; Yue, Bisong (Zootaxa, 2012)
The classification and phylogenetic relationships of the genus Blarinella have been traditionally based on morphologicalcharacteristics, and there have been no studies published about the molecular phylogenetic relationships and biogeographyfor this genus. Here, we reconstructed the phylogenetic relationships of the genus Blarinella based on one nuclear (ApoB)and two mitochondrial (cyt-b, 16S rRNA) genes. Our results supported the monophyly of the genus Blarinella and thevalid species status of Blarinella wardi. Nevertheless, two morphologically defined Blarinella species, B. quadraticaudaand B. griselda, were poorly differentiated by molecular data; B. quadraticauda was found embedded within B. griseldamaking the latter a paraphyletic group. These results indicate that B. quadraticauda might be under a budding speciationscenario or is a restricted geographical subspecies of B. griselda. Phylogeographic analyses suggest that diversificationand speciation of Blarinella might have been promoted by vicariance events associated to the complex topography of Southwest China. Further morphological, genetic and ecological studies are necessary to examine these hypotheses.